PATHOGENETIC ROLE OF THROMBOCYTES IN THE DEVELOPMENT OF AUTOIMMUNE PATHOLOGY OF THE THYROID GLAND - I. Yu. Bahmut; O. O. Halmyz; S. М. Hramatiuk; A. V. Titkova (Проблеми екології та медицини)
Taking into account the importance of platelets in the mechanisms of inflammation and the autoimmune process, the aim of this study was to experimentally answer a simple question: whether platelets in people with autoimmune euthyroidism, hyperthyroidism and hypothyroidism exhibit the characteristics of high activity. The study included 35 patients with autoimmune thyroid gland disease, positive for both TRO-Ab and Tg-Ab, and with elevated TTH, and 50 patients with elevated T4 and / or T3 concentrations and depressed levels of TTH, presence of TSHR antibodies, and / or anti-microsomal antibodies. As a result of this study, it was found that ADP-induced aggregation, that is, its parameters depend on the concentration of the aggregation inductor. According to the results of our study, we hypothesized that PMPs can interact with circulating autoantibodies and C1q involved in the formation of immune complexes, which can be a pathophysiological cause of the immune response.